Metode Tasmi’ dalam Penguatan Hafalan Al-Qur’an: Studi Kasus Yayasan Griya Fadhilah Al-Qur’an - Andriani, Nea; Muhammad Roihan Nasution; Hery Sahputra (EduInovasi: Journal of Basic Educational Studies, 2024)
Memorizing the Qur'an is not just memorizing, but being able to maintain the memorization that is owned. Nowadays, many memorizers of the Qur'an only memorize without maintaining their memorization. From here, the importance of strong memorization that must be possessed by a memorizer of the Qur'an. This study aims to identify the tasmi' method in strengthening memorization of the Qur'an at the Griya Fadhilah Al-Qur'an Foundation and to determine the supporting and inhibiting factors in strengthening memorization. This study uses a descriptive qualitative method with a field approach. Data were collected through direct observation at the Griya Fadhilah Al-Qur'an Foundation located at Jl. Amaliun No. 187, Kota Matsum II, Medan Area District, Medan City, North Sumatra and interviews with 7 informants including the leader, head of the Foundation, 2 female teachers and 3 female students. The results of the study showed that the application of the tasmi' method in strengthening the memorization of female students at Griya Fadhilah Al-Qur'an was carried out in three ways, namely tasmi' increasing juz, monthly exams, tasmi' multiples of 5 juz. The supporting factors for the application of the tasmi' method in strengthening memorization at the Griya Fadhilah Al-Qur'an Foundation are the existence of coaching from qualified teachers, self-motivation and those closest to them, a conducive and supportive environment, while the inhibiting factors are laziness, lack of time management, and lack of self-confidence.